2021
DOI: 10.48550/arxiv.2106.00866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The axial charges of proton within an extended chiral constituent quark model

Jin-Bao Wang,
Gang Li,
Chun-Sheng An
et al.

Abstract: We have performed a study of the isovector, octet and singlet axial charges of the proton in an extended chiral constituent quark model, where all the possible uudq q (q = u, d, s) five-quark Fock components in the proton wave function are taken into account. The 3 P0 quark-antiquark creation mechanism is assumed to account for the transition coupling between three-and five-quark components in proton, and the corresponding transition coupling strength is fixed by fitting the intrinsic sea flavor asymmetry d − … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In addition, the experimental data for decays of baryon resonances such as ∆(1232), P 11 (1440), S 11 (1535), S 11 (1650), D 13 (1520) and D 13 (1700) [59][60][61][62][63][64] can be also well reproduced by EχCQM. Very recently, the EχCQM has been applied to study the quark OAM of the proton and flavor-dependent axial charges of the ground state octet baryons [65][66][67]. It's shown that the singlet axial charge g (0)…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the experimental data for decays of baryon resonances such as ∆(1232), P 11 (1440), S 11 (1535), S 11 (1650), D 13 (1520) and D 13 (1700) [59][60][61][62][63][64] can be also well reproduced by EχCQM. Very recently, the EχCQM has been applied to study the quark OAM of the proton and flavor-dependent axial charges of the ground state octet baryons [65][66][67]. It's shown that the singlet axial charge g (0)…”
Section: Introductionmentioning
confidence: 99%